Typology of Stakeholder Interaction and Factors Influencing the Management of Ijen Crater Nature Tourism Park - Wahyuningtiyas, Loetvy; Rambe, Syavitri Sukma Utami; Cahyana, Alifan (Universitas Pendidikan Nasional, 2025)
The Ijen Crater Nature Tourism Park (Ijen Crater TWA) is one of the tourist destinations with the enchanting blue fire that is quite famous in East Java and even internationally. Ijen Crater has a crater lake with a very low pH, making it one of the largest acidic lakes in the world. It also has significant mineral resource potential in the form of sulfur. Not only that, but Ijen Crater is also part of the Ijen UNESCO Global Geopark. The Ijen Crater TWA is administratively located in Bondowoso and Banyuwangi Regencies, but its management is carried out by the Natural Resources Conservation Agency (BKSDA). The distribution of economic benefits tends to be unbalanced because direct fees in the form of entrance ticket sales go to the central government as Non-Tax State Revenue (PNBP). The management plan for Ijen Crater TWA is included in several development and spatial planning plans, such as the Spatial Planning (RTRW) of Bondowoso Regency, the Spatial Planning of Banyuwangi Regency, and the Long-Term Management Plan for Ijen Crater TWA. Based on these conditions, research was conducted on the typology of stakeholder interactions and the factors influencing their management using a qualitative abductive approach and pattern-matching analysis technique. The research aims to identify the interactions occurring in the Ijen Crater TWA area with the various roles held by stakeholders and to identify the factors influencing them. The research results show that the interactions in managing Ijen Crater TWA include coalitions, coordination, cooperation, networking, and coexistence. The findings from the research can be used as a consideration in developing governance strategies in infrastructure planning to spatial planning in conservation areas involving multiple stakeholders.